Annexin A1 Complex Mediates Oxytocin Vesicle Transport. (25th November 2013) - Makani, V.; Sultana, R.; Sie, K. S.; Orjiako, D.; Tatangelo, M.; Dowling, A.; Cai, J.; Pierce, W.; Allan Butterfield, D.; Hill, J.; Park, J.
<x xml:space="preserve">Abstract</x> Oxytocin is a major neuropeptide that modulates the brain functions involved in social behaviour and interaction. Despite of the importance of oxytocin for the neural control of social behaviour, little is known about the molecular mechanism(s) by which oxytocin secretion in the brain is regulated. Pro‐oxytocin is synthesised in the cell bodies of hypothalamic neurones in the supraoptic and paraventricular nuclei and processed to a 9‐amino‐acid mature form during post‐Golgi transport to the secretion sites at the axon terminals and somatodendritic regions. Oxytocin secreted from the somatodendritic regions diffuses throughout the hypothalamus and its neighbouring brain regions. Some oxytocin‐positive axons innervate and secrete oxytocin to the brain regions distal to the hypothalamus. Brain oxytocin binds to its receptors in the brain regions involved in social behaviour. Oxytocin is also secreted from the axon terminal at the posterior pituitary gland into the blood circulation. We have discovered a new molecular complex consisting of annexin A1 (ANXA1), A‐kinase anchor protein 150 (AKAP150) and microtubule motor that controls the distribution of oxytocin vesicles between the axon and the cell body in a protein kinase A (PKA)‐ and protein kinase C (PKC)‐sensitive manner. ANXA1 showed significant co‐localisation with oxytocin vesicles. Activation of PKA enhanced the association of kinesin‐2 with ANXA1, thus increasing the axon‐localisation of oxytocin vesicles. Conversely, activation of PKC decreased the binding of kinesin‐2 to ANXA1, thus attenuating the axon‐localisation of oxytocin vesicles. The result of the present study suggest that ANXA1 complex coordinates the actions of PKA and PKC to control the distribution of oxytocin vesicles between the axon and the cell body.